Government Intervention and the Improvement of Competitiveness of the National Coffee Industry: The Case of Indonesian Gayo Coffee - Riska Luneto (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2022)
This article analyses the Indonesian government's intervention to increase the competitiveness of its national coffee industry, especially one of its speciality coffees known as Gayo coffee. It aims to describe the value of Gayo coffee competitiveness based on the level of production, export volume and income of coffee farmers. In doing so, this study used Michael Porter's competitive advantage analysis which is known as the diamond model concept. The findings show that the four indicators in the diamond model concept cannot be fulfilled to make Gayo coffee a product that has competitive advantages for the government intervention was not sufficient in improving the good climate of the Gayo coffee industry. Stakeholders' cooperation in the coffee industry is needed to improve or continue the government efforts so that the Indonesian coffee industry can be competitive with the ones from other countries.